THE IMPLEMENTATION OF PROCESS-GENRE APPROACH TO TEACHING WRITING BUSINESS LETTER - Hilda Gupitasari (Journal of English and Education, 2013)
This paper reports on the results of a study on the implementation of the process-genre approach to teaching writing business letters. The study aimed to find out whether  the implementation of the process-genre approach can improve students’ ability in writing business lettersand to investigate students’ responses to the use of the process-genre approach. This study used Classroom Action Research (CAR) design and the participants were twelfth gradersat one vocational school in Cianjur. The results demonstrate improvement in students’ writing ability, evidenced in the increase in scores obtained at the end of the teaching program. Moreover, the results of the questionnaire also show the students’ consciousness that the process-genre approach could help improve their writing ability, especially writing application letters. Keywords: Process-genre approach, writing, application letter